QUASI-PERIODIC OSCILLATIONS OF SMALL-SCALE MAGNETIC STRUCTURES AND A SPECIFIC METHOD FOR MEASURING THE DIFFERENTIAL ROTATION OF THE SUN - Zhivanovich I; Solov'ev AA; Riehokainen A; Efremov VI (NAUCNO-IZDATELSKIJ CENTR INFRAM, 2025)
The SDO/HMI data with an angular resolution of 1 arcsec have been used to explore the differential rotation on the Sun, using an original p2p effect on the basis of the movement of small-scale magnetic structures in the photosphere of the Sun. It is shown that a stable p2p artifact inherent in the SDO/HMI data can be an effective tool for measuring the speed of various tracers on the Sun. In particular, in combination with the Fourier analysis, it allows us to investigate the differential rotation of the Sun at various latitudes. The differential rotation curve obtained from the SDO/HMI magnetograms by this method is in good agreement with the curves obtained earlier from groundbased observations.